Students' Knowledge Level of First Aid in Managing Minor Open Wounds - Dg Karra, Aulya Kartini; Yusuf, Saldi; Prihatini, Surya; Kurniawati; Rambu, Sitty Herliyanti (Bantayang Omni Cendekia, 2025)
Background: Minor open wounds are a common type of injury in daily life. Open wounds that do not receive proper treatment may develop into more severe conditions. A solid understanding of emergency management from an early stage is crucial to preventing the patient's condition from worsening. Objective: This study aimed to describe students' level of knowledge regarding first aid for minor open wounds. Methods: This study employed a descriptive quantitative approach with a cross-sectional design. The sampling technique used was purposive sampling, involving 39 respondents. Results: The findings indicated that students' level of knowledge about first aid for minor open wounds was in moderate category. Most students understood the basics of first aid; however, there were still gaps in knowledge regarding bleeding control and maintaining wound cleanliness to prevent infection. Conclusion: The student's level of knowledge of first aid in managing minor open wounds in this study falls within the moderate category. Further efforts are necessary to improve students' understanding of first aid, especially in managing open wounds.